Effects of surface roughness and build thickness on fatigue properties of selective laser melted Inconel 718 at 650 °C. (August 2020) - Wan, H.Y.; Luo, Y.W.; Zhang, B.; Song, Z.M.; Wang, L.Y.; Zhou, Z.J.; Li, C.P.; Chen, G.F.; Zhang, G.P.
Graphical abstract: Highlights: Fatigue strength of SLM-Inconel 718 at 650 °C was enhanced by ~50% when R a reduced from ∼14 μm to ~110 nm. Process-induced surface defects were classified as three types and simplified into idealized shape based on the quantitative characterization. The defect shape has a more severe impact on fatigue properties than the defect depth when it is less than 200 μm. Safety thresholds of stress concentration factor and defect depth are 2 and 50 μm, respectively. Abstract: Effects of the surface roughness and the build thickness on fatigue properties of selective laser melted Inconel 718 were investigated at 650 °C. The result indicated that fatigue strength was enhanced by ~50% after surface machining and polishing. The thinner un-machined specimens exhibit a longer fatigue lifetime than the thicker ones, while the opposite trend appears in the machined specimens. Finite element simulations reveal that the defect shape has more evident influence on fatigue properties than the defect depth when it is less than 200 μm. Safety thresholds of the stress concentration factor and the defect depth are 2 and 50 μm, respectively.